Decasséguis, fronteiras e dinâmicas migratórias japonesas no Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This work is a study that contemplates the realization of an erudition on the identity and the historiographical process of the Japanese families that migrated in the 1950s to the Federal Territory of Amapá (TFAP), which includes examining the occupation front in the Eastern Amazon, starting from the trajectory of their displacement throughout Brazil, with a focus on the families that were destined to populate the Amazon, including the extreme north of the country, such as Pará and the Federal Territories, who sought in some way the occupation and maintenance of the spaces in the Amazon. The study sought to analyze interviews and explore various documents and works to foster a more analytical reflection on the nuances of the topic at hand. However, the lack of documentation exploring the entire periodization of Japanese migrants (TFAP) points to an erasure of these populations and their importance in the social and historical construction of Amapá. This suggests that research on Japanese migration in the Amazon reflects a more generalized view of the permanence of these populations in these settlement colonies, often maintained with exploitative characteristics to serve national and local interests. Therefore, the aforementioned historical survey, obtained through the collection of data from various sources, proved essential in supporting the production, in conjunction with ANIBRAP, of the "Memorial of Japanese Immigration of Amapá," which will become a museum built in the state under the supervision of the municipality, as an inaugural landmark of Japanese migration to Amapá, contributing to a new perspective and historicity within the contributions of History and Social Sciences.
Keywords: Migração internacional; Imigração japonesa - Ocupação territorial; Diáspora japonesa; CNPQ::CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL; ODS 4 – Educação de qualidade; ODS 10 – Redução das desigualdades; ODS 11 – Cidades e comunidades sustentáveis